2021
DOI: 10.1108/intr-10-2020-0557
|View full text |Cite
|
Sign up to set email alerts
|

Catch me if you can: effects of AR-enhanced presence on the mobile game experience

Abstract: PurposeThe purpose of the present research was to examine the effects of content, spatial, temporal and social presences stimulated by augmented reality (AR) technology on game enjoyment and continuing behavioral intention.Design/methodology/approachA total of 355 mobile AR game players participated in an online survey posted via the nationwide crowdsourcing web service in the US. A structural equation modeling was conducted using a maximum-likelihood estimation procedure to test the relationships among the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…Most prior studies [47,48,53,56] supported the concept that IM provides several unique features for their users to enhance social presence, such as different encoding mode, updating status, transmitting voice message etc., which eventually influence IM adoption in the organizational communication context. Many prior studies tried defining social presence based on how employees are able to project their social presence and emotion to one another in a collaborative communication environment [57][58][59][60]. In relation to this perspective, symbol set is considered as one of the media features that allow users to interact and express their emotion.…”
Section: Symbol Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Most prior studies [47,48,53,56] supported the concept that IM provides several unique features for their users to enhance social presence, such as different encoding mode, updating status, transmitting voice message etc., which eventually influence IM adoption in the organizational communication context. Many prior studies tried defining social presence based on how employees are able to project their social presence and emotion to one another in a collaborative communication environment [57][58][59][60]. In relation to this perspective, symbol set is considered as one of the media features that allow users to interact and express their emotion.…”
Section: Symbol Setmentioning
confidence: 99%
“…Symbol set can be described as a different way of encoding information to transmit to receivers. Encoding, the first step of communication, starts with the selection of words, symbol, voice, picture and the like by the senders that is transmitted to the receivers [37,[58][59][60][61][62]. Similarly, there are four forms of symbol set that humans can apply for their day-to-day communication including physical, visual, verbal and written [5,14,19,63].…”
Section: Symbol Setmentioning
confidence: 99%
See 1 more Smart Citation
“…ose who are addicted to video games are incapable of controlling their actions because of their excessive gaming. In addition, DMS-5 and ICD-II now include IGD, but the issue of addiction is still up for debate [9]. According to DSM-5, "gamers" are people who spend all of their free time on the Internet playing video games.…”
Section: Introductionmentioning
confidence: 99%
“…In their review of factors associated with engagement in health-related games,Schwarz et al (2020) identified various elements of realism that are important. These included relatable characters(Park and Ko, 2022), a realistic narrative storyline and high-quality graphics Adobor and Daneshfar (2006). concurred, finding that unrealistic games reduce user motivation to play management games whilstBeckem and Watkins (2012) stressed the importance of an immersive environment that closely represents the complexity of the working context Lee et al (2020).…”
mentioning
confidence: 99%